INNOVATIVE VOCABULARY TEACHING: THE EFFECTIVENESS OF ASSEMBLR EDU APP IN JUNIOR HIGH SCHOOL CLASSROOMS - Muhammad Fatkhul Hikam; Nurhayati Ganinda; Rini Lindawati (Adisam Publisher, 2025)
This study aims to determine the effectiveness of using the Assemblr Edu application as a vocabulary learning media and describe the response of seventh- grade students of SMPN 1 Gedeg Mojokerto to the media. This research is quasi- experimental research with a Non-equivalent Group design. The data collection techniques used were tests and questionnaires. Data collection tools used student worksheets and questionnaire sheets. The location of this research was SMPN 1 Gedeg, Gedeg District, Mojokerto Regency, East Java Province with a population of VII grade students as many as 256 students. The sample used was 64 students, with 32 students in the experimental class who used Assemblr Edu App media and 32 students in the control class who did not. The results showed that the use of learning media was effective as a media for vocabulary learning, with a t-test value of t = 4.127 and a significance of 0. Students' responses to this application were positive in cognitive (content knowledge 81.8%, understanding of use 81.6%, understanding of presentation 82.6%) and affective (motivation 78.1%, interest 82.8%, curiosity 81.3%) aspects. This shows that the Assemblr Edu application is effective in learning English, especially vocabulary material.